Innovative Ideas in Entrepreneurship : Key Issues, Challenges and Future Scope - Anusha, Vunnam (AMC Indian Journal of Entrepreneurship, 2021)
COVID-19 situation has affected economies of a large number of countries. The only way to overcome the economic crisis is by increasing exports which can be accomplished by establishing new business and encouraging new talents. Due to COVID-19 situation, large companies have problems with cash-flow management while small businesses are shutting down. So, looking at this situation, will business management students back out from entrepreneurship ? This study helped us know how this pandemic affected future entrepreneurs and factors influencing future entrepreneurs. This paper helped us to know the challenges future entrepreneurs are going to face, future scope of entrepreneurship, and a career option an individual is adopting based on past life experiences. The government is encouraging entrepreneurship with new schemes like Make in India, Udyam schemes etc. Though there is lot of encouragement from government and private investors, it is a bit difficult and challenging to get financial support. This paper gives detailed information about Udyam Scheme and percentage of people getting financial support from the amount released by the Indian government at the center through this scheme. The study was based on primary data backed up by secondary data to know facts about financial support from the government. To explain relationship between personal factors and interest of future entrepreneurs, ANOVA test was used. Non-parametric test was used to know the relationship between different phases of the business and participation in startup summits.